2023
DOI: 10.1101/2023.10.25.23297575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Navigating vaccination choices: The intersecting dynamics of institutional trust, belonging and message perception among Congolese migrants in the UK (A reflexive thematic analysis)

Alison F Crawshaw,
Tushna Vandrevala,
Felicity Knights
et al.

Abstract: Background The COVID-19 pandemic has disproportionately impacted intersectionally marginalised migrants, revealing systemic disparities in health outcomes and vaccine uptake. An in-depth understanding of the underlying social and structural factors influencing health behaviours is necessary to develop tailored interventions for migrants but has been seldom explored. Therefore, this qualitative study aimed to explore the contextual factors shaping COVID-19 vaccination decision-making among Congolese migrants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…to influence the health decision-making process. 48 Our findings align with other research which highlights preferences for face-to-face 58,59 and oral communication 60,61 among migrant populations, as well as strategies that build or reinforce trust. 59,62,63 They also align with systematic reviews that have indicated that culturally adapted interventions may be effective in community settings.…”
Section: Disseminationsupporting
confidence: 90%
“…to influence the health decision-making process. 48 Our findings align with other research which highlights preferences for face-to-face 58,59 and oral communication 60,61 among migrant populations, as well as strategies that build or reinforce trust. 59,62,63 They also align with systematic reviews that have indicated that culturally adapted interventions may be effective in community settings.…”
Section: Disseminationsupporting
confidence: 90%